Diagnóstico de la cogeneración de energía eléctrica en la planta extractora de aceite de una empresa agroindustrial de palma africana de la ciudad de san francisco de Orellana durante el año 2015. Diseño un sistema hibrido eficiente para la generación energética eléctrica. - Jimenez Chafla, Marcela Adriana (2018)
The present thesis project, aims to determine the magnitude of the electrical potential in African Palm Agro-industrial Company at San Francisco de Orellana City, which comes from the electricity generation that is produced. The parameters to consider during the design are the energy co-generation by bio-mass that is performed through a turbine, the bio-mass is inserted in a boiler, which evaporates on a large amount of water, the steam produced is used in the different production processes of palm oil, the excess steam is used to generate electricity, as well as a conventional thermo-electric. The insufficient co-generation of electrical energy influences the production processes losing efficiency, efficacy and effectiveness in the oil extraction, as if it solves this problem will improve the quality level, at the lowest possible cost and with the capacity to respond to the demands generated by their customers. A hybrid system is designed using different technologies; in this case, the co-generation by bio-mass, the public electricity network and the two diesel generators are applied. Thus, climatic and economic reasons are the most feasible. The thesis project is intended to provide an efficient hybrid system of power generation, through the current situation analysis, to the agro-industrial company requirements and by the programs use that simulate an optimal system. In this way, HOMER Pro is used which is a software that has as a tool the fuel by bio-mass and cost energy analysis for implementation. As a result of this work we present the design of the hybrid system with all its parameters and records that were obtained from the exploratory research applied in the extraction plant an increase in energy potential between 800 KW to 1000 KW, at a cost per KW / h of approximately $ 0.10 ctv. depending on the duration of the project, with the cost analysis it is determined that the project is viable with an IRR of $ 10,981,834.54 dollars and a NPV of $ 10,405,205,55 dollars to a maximum time of 30 years for their recovery, with these data management can make the best decision for its implementation.